Are Children in Growing Danger of Social Exclusion? Evidence from Italy and Spain - Conchita D'Ambrosio; Carlos Gradín (Luxembourg Income Study (LIS), 2000)
In this paper, we claim that children are in danger of social exclusion both in Italy and in Spain since social distance between age groups has increased over time. We use as a measure of social exclusion an index of polarization since neither the Lorenz-consistent inequality indices nor the measures of poverty are suited to this task. We look for the causes of this phenomenon by grouping children according to some characteristics of the household to which they belong. Our last aim is to measure the effects that government intervention has had on this phenomenon. We focus on public provisions of education and health care. One of the main findings is that public intervention was not at all successful in fighting this phenomenon, since welfare state institutions of the two countries were designed to combat risks associated with old age and not with childhood.
Keywords: 330; Jugendliche; Soziale Isolation; Einkommensverteilung; Armut; Italien; Spanien